2022
DOI: 10.20452/pamw.16323
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome following COVID-19: underestimated consequence of infection with SARS-CoV-2

Abstract: The present paper is, to our knowledge, the first one to reveal persistent gastrointestinal symptoms following COVID-19, which are frequent and account for a significant and growing attention among gastroenterologists and other healthcare practitioners. The Rome IV criteria may not address the full spectrum of GI symptoms following COVID-19, which is related to the presence of a significant time criterion. In addition to the common stress of isolation, another possible cause of the problem is that the microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 29 publications
0
20
0
3
Order By: Relevance
“…Of the 20 records selected, five studies were excluded for reporting FD or IBS without using Rome criteria, [26][27][28][29][30] three for reporting FD or IBS rates without reporting COVID-19 diagnosis, [31][32][33] one for reporting FD and IBS in children 34 and one for inability to extract number of subjects and/or number of events from cases. 35 Thus, a total of 10 studies, [12][13][14][36][37][38][39][40][41][42] all full texts, met the eligibility criteria and were included in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 20 records selected, five studies were excluded for reporting FD or IBS without using Rome criteria, [26][27][28][29][30] three for reporting FD or IBS rates without reporting COVID-19 diagnosis, [31][32][33] one for reporting FD and IBS in children 34 and one for inability to extract number of subjects and/or number of events from cases. 35 Thus, a total of 10 studies, [12][13][14][36][37][38][39][40][41][42] all full texts, met the eligibility criteria and were included in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…37 The median age of patients included ranged from 29 14 to 68 years. 42 Four studies were carried out in North America, [36][37][38][39] three in Europe 12,13,42 and three in the Middle East and Asia. 14,40,41 Four studies had a retrospective design, 13,[36][37][38] four studies a prospective design, 12,[39][40][41] one study reported a prospective COVID-19 group and a retrospective control group 14 and one study reported on prospectively assessed data on a retrospective cohort.…”
Section: Study Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postcovid Irritable Bowel Syndrome, P-IBS) [5,6]. Wciąż jednak, z powodu niewielkiej liczby badań w omawianym zakresie, brakuje jednoznacznego wskazania na mechanizmy, profilaktykę i leczenie P-IBS [1,5,7,8,72,73].…”
Section: Wprowadzenie I Cel Pracyunclassified